Your SlideShare is downloading. ×
Derivación por regla de la cadena
Derivación por regla de la cadena
Derivación por regla de la cadena
Upcoming SlideShare
Loading in...5
×

Thanks for flagging this SlideShare!

Oops! An error has occurred.

×
Saving this for later? Get the SlideShare app to save on your phone or tablet. Read anywhere, anytime – even offline.
Text the download link to your phone
Standard text messaging rates apply

Derivación por regla de la cadena

1,443

Published on

Published in: Education
0 Comments
0 Likes
Statistics
Notes
  • Be the first to comment

  • Be the first to like this

No Downloads
Views
Total Views
1,443
On Slideshare
0
From Embeds
0
Number of Embeds
0
Actions
Shares
0
Downloads
5
Comments
0
Likes
0
Embeds 0
No embeds

Report content
Flagged as inappropriate Flag as inappropriate
Flag as inappropriate

Select your reason for flagging this presentation as inappropriate.

Cancel
No notes for slide

Transcript

  • 1. Derivación por regla de la cadenaEjercicio #1 3 3y = sen x = (Senx)Haciendou = Senx => = cosxEntonces 3 2Y=u => = 3uAhora 2 = = 3u CosxHaciendo el remplazo de uObtenemos que: 2 = 3 sen x cosx
  • 2. Ejercicio # 2 5F (x) = Cos xHaciendo 5W = X => = 5x4EntoncesF (w) = Cosw => = —senwAhora 4 = = —Senw 5xHaciendo el remplazo y organizandoObtenemos que: 4 5 = —5x Sen x
  • 3. Ejercicio # 3 7 4Y = tg xHaciendo 4 3r = x => = 4x 2Z = tgr => = Sec rEntonces 7 6Y = z => = 7zAhora 6 2 3 = = 7z Sec r 4xHaciendo el remplazo y organizandoObtenemos que: 6 2 4 3 = 7 (tgr) Sec (x ) 4x 3 6 4 2 4 = 28x tg x Sec x

×